2010
DOI: 10.1002/ps.1983
|View full text |Cite
|
Sign up to set email alerts
|

Thrips (Thysanoptera: Thripidae) mitigation in seedling cotton using strip tillage and winter cover crops

Abstract: Growers who utilize strip tillage and a winter cover crop can utilize seed treatments for mitigation of early-season thrips infestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
2
24
2
Order By: Relevance
“…In addition, All et al (1993) reported cotton seedlings had higher thrips densities in areas that had native winter vegetation compared with areas that had winter wheat as a cover crop. Toews et al (2010) found no differences in thrips densities between three cover crops (rye, Secale cereale L.; wheat, Triticum aestivum L.; and crimson clover, Trifolium incarnatum L.).…”
Section: Impact Of Cultural Practices Thrips Populationsmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, All et al (1993) reported cotton seedlings had higher thrips densities in areas that had native winter vegetation compared with areas that had winter wheat as a cover crop. Toews et al (2010) found no differences in thrips densities between three cover crops (rye, Secale cereale L.; wheat, Triticum aestivum L.; and crimson clover, Trifolium incarnatum L.).…”
Section: Impact Of Cultural Practices Thrips Populationsmentioning
confidence: 76%
“…All et al (1992) reported that tobacco thrips densities were significantly lower in no-till treatments than in conventional till treatments. Toews et al (2010) observed that thrips densities were lower in plots managed using strip till practices compared with plots managed using conventional tillage practices. In addition, All et al (1993) reported cotton seedlings had higher thrips densities in areas that had native winter vegetation compared with areas that had winter wheat as a cover crop.…”
Section: Impact Of Cultural Practices Thrips Populationsmentioning
confidence: 91%
“…Similarly, in conservation tillage plots the cotton had outgrown whatever protection was conferred by rolled rye cover; however, the taller standing rye continued to protect cotton from infestation by adult thrips. Toews et al (2010) showed that increasing density of ground cover decreased thrips infestations; these data suggest that the three dimensional structure of the standing ground cover may also play a role in thrips suppression.…”
Section: Discussionmentioning
confidence: 90%
“…The 2013 data suggested that thiamethoxam decreased immature thrips populations for the first two sample dates; however, this effect was not evident in the 2014 data. Previous studies (All et al, 1992;Bauer and Roof, 2004;Brandenburg et al, 1998;Hurt et al, 2005;Manley et al, 2003;Olson et al, 2006;Toews et al, 2010) document a decrease in thrips and virus incidence in reduced tillage systems. Here, we observed similar results in 2013 but not in 2014; however, virus incidence was very low in 2014 compared to 2013.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation